Post-graduate Students’ Feedback on District Residency Program: A Cross-sectional Study (GAIMS Journal of Medical Sciences, 2024)
IntroductionThe District Residency Program (DRP) was implemented by National Medical Commission (NMC) for post graduate (PG) students from Batch 2021 onwards. All students of Batch 2021 and some students of Batch 2022 have completed their DRP posting in one year. This survey was conducted with the objective to get the feedback of students and identify the areas, if any, that require attention of the stakeholders for further improvement in the implementation of the program.MethodologyIEC approval was taken before starting this study. An online questionnaire (Annexure-1) was prepared and validated. It was sent to 55 PG students of our institute who completed the DRP posting. The responses so collected were tabulated in Microsoft Excel sheets and statistical analysis was done.ResultsOut of 55 PG students, 37 responded to the online questionnaire. Thirty-three (89.1%) students felt that they received their subject specific training at least to some extent during DRP posting. This perception was significantly more in students of surgical specialties as compared to their medical counterparts (p=0.0276). Sixteen (43.2%) students did not feel that their skills were enhanced. Fourteen (37.8%) students didn’t feel motivated and confident after the posting. Nineteen (51.3%) students were not satisfied with the basic amenities provided to the during the posting. Eighteen (48.6%) students felt isolated from the parent institute and sixteen (43.2%) students never participated in the teaching activities of parent institute through online mode. Twenty-four (64.8%) students felt that the duration of DRP posting should be less than 3 months.ConclusionsDRP is an ambitious program to enhance exposure and orientation of PG students to community health needs in district health care delivery system. Every effort should be made by stakeholders to provide good basic amenities to the students. Posting PG students at centers where specialists in respective subjects are available will generate sufficient clinical material to meet their training needs. The parent department should be in regular contact with the students and motivate them to actively participate in the departmental teaching activities through online platforms.